Redes sociales y decisión de compra de paquetes turísticos por parte de los clientes nacionales del tour operador Iquitos Experience Tours EIRL en Iquitos 2024 - Rojas Chavez, Joycelinz Mayra (2025)
This research aimed to determine the relationship between the use of social media and the decision to purchase tourist packages by national clients of Iquitos Experience Tours E.I.R.L. in Iquitos, during 2024. It was an applied study with a quantitative approach and a non-experimental cross-sectional design. The sample consisted of 150 clients, to whom a structured questionnaire was applied. Statistical analyses, including the Spearman's Rho test and Chi-square test, showed no significant relationship between the use of social media and the decision to purchase (p > 0.05). Despite the frequent use of social media among clients, these results suggest that social media is not a determining factor in the purchasing decision. It is recommended that tourism sector actors consider other factors such as brand trust or previous customer experience to improve commercial strategies.